From the Loser to the Winner - How Trade Liberalization can lead to Leapfrogging between Countries - Christian Rutzer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
How shifts in the economic leadership between countries can occur has been widely debated not only since the recent catch up of China in several sectors. However, there is no adequate theoretical model analyzing this question in the light of trade liberalization. This paper is the first one to address productivity leapfrogging between two countries using a heterogeneous firms trade framework. In the model, firms' R&D investments determine their expected productivity draw. In one country firms face lower R&D costs. Before trade liberalization, the sector productivity and the competition intensity is higher in this country. However, when trade liberalization occurs, fiercer competition can more than offset the investment advantage. Hence, firms from the disadvantaged country may invest relatively more in R&D than firms from the advantaged country. Consequently, the laggard country can become the leader in terms of sector productivity after trade liberalization. The results of the model highlight open markets in combination with innovations by firms as the necessary requirement for leapfrogging between two countries.
Keywords: F12; F13; F10; 330